Mesenchymal Stromal Cell Therapy in Novel Porcine Model of Diffuse Liver Damage Induced by Repeated Biliary Obstruction - Vištejnová, Lucie; Liška, Václav; Kumar, Arvind; Křečková, Jana; Vyčítal, Ondřej; Brůha, Jan; Beneš, Jan; Kolinko, Yaroslav; Blassová, Tereza; Tonar, Zbyněk; Brychtová, Michaela; Karlíková, Marie; et al. (International journal of molecular sciences, 2021)
In liver surgery, biliary obstruction can lead to secondary biliary cirrhosis, a life-threatening disease with liver transplantation as the only curative treatment option. Mesenchymal stromal cells (MSC) have been shown to improve liver function in both acute and chronic liver disease models. This study evaluated the effect of allogenic MSC transplantation in a large animal model of repeated biliary obstruction followed by partial hepatectomy. MSC transplantation supported the growth of regenerated liver tissue after 14 days (MSC group, n = 10: from 1087 ± 108 (0 h) to 1243 ± 92 mL (14 days); control group, n = 11: from 1080 ± 95 (0 h) to 1100 ± 105 mL (14 days), p = 0.016), with a lower volume fraction of hepatocytes in regenerated liver tissue compared to resected liver tissue (59.5 ± 10.2% vs. 70.2 ± 5.6%, p < 0.05). Volume fraction of connective tissue, blood vessels and bile vessels in regenerated liver tissue, serum levels of liver enzymes (AST, ALT, ALP and GGT) and liver metabolites (albumin, bilirubin, urea and creatinine), as well as plasma levels of IL-6, IL-8, TNF-α and TGF-β, were not affected by MSC transplantation. In our novel, large animal (pig) model of repeated biliary obstruction followed by partial hepatectomy, MSC transplantation promoted growth of liver tissue without any effect on liver function. This study underscores the importance of translating results between small and large animal models as well as the careful translation of results from animal model into human medicine.
Keywords: hepatectomy; cholestáza; secondary biliary cirrhosis; mesenchymal stromal cell; Mesenchymal Stem Cell Transplantation; Disease Models, Animal; Mesenchymal Stem Cells; transplantace mezenchymálních kmenových buněk; quantitative histology; nemoci jater; Swine; mezenchymální kmenové buňky; pig model; modely nemocí na zvířatech; zvířata; Liver Diseases; Cholestasis; prasata; Animals